ANALYSIS OF REGIONAL CASH RECEIPTS AND EXPENDITURES ACCOUNTING INFORMATION SYSTEMS IN IMPROVING THE INTERNAL CONTROL SYSTEM: (CASE STUDY OF THE MUNICIPAL FINANCIAL AND REGIONAL REVENUE MANAGEMENT AGENCY SUKABUMI) - Zahwa Syafira, Dania; Wahyu Nugroho, Gatot; Sofiani, Venita (Penerbit Lafadz Jaya, 2023)
This research aims to determine and explain the accounting information system for cash receipts and disbursements as an effort to improve internal control at BPKPD Sukabumi City. The method used is descriptive qualitative with triangulated data collection, namely observation, interviews and documentation; and also data analysis techniques for data reduction, data presentation and conclusions. The research results concluded that the internal control system for cash receipts and disbursements was running well, this was assisted by the implementation of the PANTAS and SIPKD applications to make it easier for users to produce information that was effective, efficient, transparent, auditable and accountable. Apart from that, it can also be seen from the implementation of the accounting information system for cash receipts and disbursements which is in accordance with Permendagri Number 77 of 2020 concerning